Morphological diversity of piquin chilli (Capsicum annuum L. var. glabriusculum) from Querétaro and Guanajuato, Mexico - Ramírez Novoa, Uriel Israel; Cervantes Ortiz, Francisco; Montes Hernández, Salvador; Raya Pérez, Juan Carlos; Cibrián Jaramillo, Angélica; Andrio Enriquez, Enrique (Revista Mexicana de Ciencias Agrícolas, 2018)
In the present investigation, the morphological variability of 11 populations of wild piquin chili (Capsicum annuum var. glabriusculum) of the Mountain range Gorda and Semidesert of Queretaro (Municipalities of Arroyo Seco, Jalpan of Serra, Toliman and Cadereyta de Montes) and Guanajuato (Municipality of Xichu). The characterization was carried out under greenhouse conditions at the Technological Institute of Roque (ITR) located in Celaya, Guanajuato, Mexico. The 44 characters were recorded in seedling, plant, flowering, fruit maturity and seed. The principal component analysis (CP) showed that the first three components explained 56.6% of the total morphological variability. The CP1 was explained by the characteristics of weight (0.326), width (0.301) and fruit length (0.271), leaf density (0.277) and seed diameter (0.297). In CP2, the variables that contributed most to the expression of the variation were width (0.329) and leaf pubescence (0.317) and finally, in CP3, the shape of the fruit (0.344) and color of the anthers (-0.308) were the most important characters. On the other hand, the cluster analysis generated four groups, group I included the G3 (Rosa of Castilla), G2 (Palmitas The Tanque), G1 (The Tanque) populations, all of the Mountain range Gorda in Guanajuato. Group II was made up of population Q7 (The Patol, Querétaro). Group III was formed by population Q5 (Presa Jalpan, Querétaro) and finally, group IV was integrated by six populations, Q4 (San Antonio Tancoyol), Q8 (Higuerillas stream), Q6 (Higuerillas The Shote), Q2 (The Refugio solar-huerta), Q3 (Tancoyol Road to Tancoyol) and Q1 (The Chilar Refuge), all of the State of Querétaro. The morphological diversity found in this species tells us that this native plant should be conserved and that it can be easily integrated into a program of sustainable use of the flora of the region.